Characterization and Potential Utilizations of A Marine Euglenophyte from Okinawa, Japan - Prabowo, Danang Ambar; Suda, Shoichiro (:Agency for Marine and Fisheries Research and Human Resources, Indonesia, 2024)
mong many microalgae species, certain euglenophytes stand out asexcellent sources of valuable natural components with diversebiotechnological applications. This study focused on investigating the identityand potential utilizations of a green marine euglenophyte, namely EKoku01,isolated from the brackish Kokuba River in Naha City, Okinawa, Japan.Morphologically, cells of EKoku01 were 12-30m long and 8-10 m wide,displaying dynamic changes during euglenoid motility with a distinctivelystriated pellicular body. Notable features included two uneven flagella, aneyespot, and multiple green discoid chloroplasts. The 18S rDNA molecularphylogeny positioned Ekoku01 within Clade 1 of Eutreptiella, comprisingstrain CCMP389, CCMP-1594, and LIS 2000, which was distantly related toother known marine euglenophytes (i.e., the genus Eutreptia and Clade 2 ofEutreptiella). Based on the morphology and molecular phylogeny, EKoku01was identified as Eutreptiella sp., representing the first recorded species ofthis genus in Okinawa, Japan. EKoku01 showed an optimum growthperformance at 20 oC (max. =0.17 ± 0.037 day-1) and exhibited an unusuallystrong positive phototaxis response towards a light source. Its fatty acid (FAs)profile comprised predominantly saturated FAs (69.8%), polyunsaturated FAs(15.1%, with two omega-3 FAs), monounsaturated FAs (3.6%), and branchedFAs (4.4%), while 7.1% remaining unidentified. Based on its growthperformance, FAs composition, and light sensitivity, we proposed severalpotential utilizations of this strain (e.g., as a source for nutraceutical,pharmaceutical, food, and aquaculture applications), including the use ofEKoku01 as a model organism for developing an innovative light-driven cellconcentration system based on phototaxis.